Understanding the Role of Indigenous Peoples in Preserving Cianjur Pandanwangi Rice as a Product of Local Wisdom to Obtain Geographical Indication Certificates - Ismail Rumadan; Pri Pambudi Teguh; Umar Husin; Ummu Salamah; M. Rendi Aridhayandi; Yuyun Yulianah (Fakultas Hukum, Universitas Warmadewa, 2022)
Pandanwangi Cianjur rice which has a distinctive taste, as good quality rice because it is the result of rice varieties with special characteristics that are influenced by geographical and cultural conditions from Cianjur blood so that Pandanwangi rice is categorized as a product of local wisdom in Cianjur Regency and has received a Geographical Indication certification. (IG) from the Ministry of Law and Human Rights of the Republic of Indonesia. However, the ownership of this certificate does not guarantee an increase in the economy that is exploited from Pandanwangi rice because the Regional Government has not provided maximum assistance and guidance so that the community takes advantage of the potential of Pandanwangi rice as an economically viable source of income. Therefore, it is necessary to socialize and foster from various parties, especially from academics through community empowerment activities to understand the existence of Cianjur pandanwangi rice as part of local wisdom products so that it is maintained as a cultural value and can provide economic benefits for the local community.